TINGKAT KESEGARAN JASMANI SISWA KELAS 11 SMK BHAKTI PRAJA ADIWERNA KABUPATEN TEGAL TAHUN 2012 (Department of Physical Education, Sport, Health and Recreation, 2013)
Physical fitness required by humans according to their activities, one of which is the students of SMK BhaktiPraja Adiwerna are faced with activities and environmental conditions that are less healthy from unhealthyhabits and irregular with a supported environment of about SMK Bhakti Praja Adiwerna unhealthy then willaffect the posture and physical condition. The problem in this research is how the status of physical fitness levelof students of SMK Bhakti Praja Adiwerna Tegal regency in 2012. The purpose of this study was to determinethe status of the physical fitness level of students of SMK Bhakti Praja Adiwerna Tegal regency in 2012.Thisstudy is a survey research. The population in this study were students in grade 11 SMK Bhakti Praja Tegalregency in 2012, amounting to 45 people, and the sample used in this study were 45 students taking the sampleusing total sampling technique. Variable in this study is the level of physical fitness. The research instrumentused was a physical fitness tests children aged 12-15 years. Analysis of the data in this study is the percentage ofdescriptive data analysis.Based on the analysis of the data obtained from the results that the overall results of physical fitness tests SMK Bhakti Praja Grade 11 students who are not in either category ermasuk all, 11students (24.44%) included in either category, 29 students (64.44%) included in the medium category, 5students (11.11%) included in the category of less and no students are included in the category of less than once.This is because the class X students of SMK Bhakti Praja always physical exercise and they are also active inextracurricular sports activities organized by the school. Conclusions based on the results of the study is the levelof physical fitness grade 11 SMK Bhakti Praja Adiwerna mostly included in the criteria being. Advice from theresearch results that can be given is the teacher providing guidance to students in order to maintain, improvephysical fitness with regular exercise activities and also implement a healthy lifestyle, and the school principalshould be able to seek adequate facilities to maintain and improve physical fitness levels of all students .